Social media use disorder is associated with higher BMI and negative eating behaviors, whereas mindful eating has a protective effect - Bayindir Gumus, Aylin; Eser Durmaz, Sevinc; Nisanci Kilinc, Fatma; Ozenir, Ciler; Cakir, Biriz; Acik, Murat (Emerald Group Publishing Ltd, 2025)
PurposeThis study aimed to examine the relationship between body mass index (BMI), the social media use disorder scale (SMUDS) and scale of effects of social media on eating behaviour (SESMEB) and to test the mindful eating questionnaire (MEQ) as a potential mediator.Design/methodology/approachIn this cross-sectional study, 2,296 (45.0%) males and 2,804 (55.0%) females, 5,100 adults in total, between 18 and 64 years old through an online survey via social media platforms. Participants were mostly single (69.9%), undergraduates (78.1%), and living in urban areas (78.9%). IBM-AMOS was used to explore whether mindful eating mediated the associations between social media parameters and BMI.FindingsThe structural equation modeling (SEM) showed that enforcement affects five sub-dimensions of mindful eating, and escape affects emotional eating and interference. Operation and escape dimensions of SMUDS had an indirect effect by affecting mindful eating, 3.1% of the total effect on BMI change. The direct effect of MEQ and SMUDS scores on BMI was found to be statistically significant (beta = -0.196 and -0.152, respectively), but the relationship between SESMEB and BMI was not significant. SMUDS indirectly affected 21.4% of the total effect in BMI change, contributing to the development of the MEQ.Originality/valueSocial media use disorder has been associated with increased BMI and unhealthy eating behaviors. The present study revealed that social media use disorder is associated with increased BMI, and increased mindful eating might play a protective role against obesity. On the other hand, it is important to recognize that obesity is a complex biopsychosocial phenomenon influenced by multiple risk factors, and the underlying processes are highly intricate.
Keywords: Social media use disorder; Mindful eating; Obesity; Addiction